Penerapan Komputer Di Dusun Tebangan B, Desa Kampung Baru, Kabupaten Labuhan Batu, Provinsi Sumatra Utara The Role of Computers In The Countryside - Antoni Pribadi (Jurnal Sains dan Ilmu Terapan, 2021)
This research is motivated by the indications of low computer literacy in rural communities which makes it difficult to become part of the information society. The study was designed to determine the extent to which the level of computer literacy in rural communities and the factors indicated to affect the level of computer literacy in rural communities. The research was carried out using a survey method of respondents in the rural community of New village, Tebangan Hamlet (Labuhan Batu Regency) North Sumatra Province.